PENGARUH SELF CONGRUITY TERHADAP NIAT PERILAKU DENGAN EXPERIENTIAL VALUE SEBAGAI VARIABEL MEDIASI (PADA WISATAWAN DESTINASI WISATA KOTA BANDA ACEH) - Ella Putri Maghfira, Farid (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2016)
This aims of this study are to investigate the effect of self congruity, and experiential value on behavioral intentions. The tourist destination city of Banda Aceh travel is a taken as a sample in this study. The method of this study employed questionnairs as an instrument. Total sampling is applied as the study’s convenience technique. Hierarchical Linear Modelling methods of analysis are used to determine the influence of the variables involved. The results of this study indicate that self congruity have positive effect on behavioral intentions, self congruity have positive influence on experiential value and experiential value positive effect on behavioral intentions. This study also shows that self congruity influential significantly against experiential value nor against behavioral intentions. In addition abtained results that experiential value has partial mediated the effect of self congruity effect to behavioral intentions.  Keywords: Self Congruity, Experiential Value, Behavioral Intentions